Using Role, Audience, Format, and Topic (RAFT) in Teaching Writing - Ratih Anggraini; Bustami Usman (Universitas Syiah Kuala, 2017)
This study was a quantitative research about the implementing of Role, Audience, Format, and Topic (RAFT) strategy used in teaching writing descriptive text. The participant of this study was the students from second grade of Junior High School: SMP 10 which divided into the experimental group and the control group. They were chosen by using simple random sampling. The reason for conducting this study was due to the fact that students’ writing skill was still low. Moreover, the design used in this study was true experiment with pre-test-post-test control group design. The data was collected through pre-test, treatment, and post-test. The findings showed that mean of post-test of experimental class (=62.35) was higher than mean of post-test of control class (=44.3). The result of t-score of experimental class (=9.16) was higher than t-score of control class (=4.87) with the level of significance (=0.05). Hence, it can be concluded that Role, Audience, Format, and Topic (RAFT) can improve the students’ writing skill in descriptive text.